Neuroprotective effect of N-acetylcysteine against cisplatin-induced toxicity in rat brain by modulation of oxidative stress and inflammation - Abdel-Wahab WM; Moussa FI (Dove Medical Press, 2019)
Wessam M Abdel-Wahab,1,2 Farouzia I Moussa1 1Department of Zoology, Faculty of Science, University of Alexandria, Alexandria, Egypt; 2Department of Basic Sciences/Biology Unit, Deanship of Preparatory Year and Supporting Studies, Imam Abdulrahaman Bin Faisal University, Dammam, Saudi Arabia Background: Neurotoxicity is a major obstacle to the effectiveness of cisplatin (CDDP) in cancer chemotherapy. Oxidative stress and inflammation are considered to be the major mechanisms involved in CDDP-induced neurotoxicity. The rationale of our study was to investigate the efficacy of N-acetylcysteine (NAC) at two different doses in the management of CDDP-induced toxicity in rat brain by monitoring its antioxidant and anti-inflammatory effects.Methods: Thirty-five male rats were divided into five groups (n=7) as follows: control group (0.5 mL saline), NAC100 group (100 mg/kg), CDDP group (8 mg/kg), NAC50-CDDP group (50 mg/kg NAC and 8 mg/kg CDDP), and NAC100-CDDP group (100 mg/kg NAC and 8 mg/kg CDDP). NAC was administered for 20 consecutive days, while CDDP was injected once on day 15 of the treatment protocol.Results: The neurotoxicity of CDDP was evidenced by a marked increase in acetylcholinesterase and monoamine oxidase activities. It also induced oxidative stress as indicated by increased levels of lipid peroxidation, nitric oxide, and protein carbonyl with a concomitant decline in reduced glutathione, glutathione peroxidase, glutathione S-transferase, superoxide dismutase, and catalase in the brain. Moreover, CDDP enhanced the synthesis of pro-inflammatory cytokines such as tumor necrosis factor-α, interleukin-1β, and interleukin-6. Treatment with NAC at the two selected doses significantly attenuated CDDP-induced changes in the brain cholinergic function, improved the brain oxidant/antioxidant status, and also reversed the overproduction of pro-inflammatory cytokines in brain and serum.Conclusion: NAC could serve as an appropriate and safe complementary therapeutic agent to attenuate the toxicity of CDDP in the brain and therefore improve its outcomes in chemotherapy. Keywords: cisplatin, neurotoxicity, brain, N-acetylcysteine, rats